Efisiensi Metode Problem Solving dan Course Review Horay (CRH) Pada Pembelajaran Matematika Bagi Siswa Sekolah Dasar - Yunita Wildaniati (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
Mathematics is a very important subject to be taught in SD / MI because mathematics is very useful in the daily lives of students and is needed as a basis for learning advanced mathematics and other subjects. Problem Solving is an effort to find a way out that is done in achieving the goal (learning outcomes), by understanding the elements that are known, asked, and the adequacy of the elements needed, able to make or compile mathematical models, can choose and develop strategies for solving, able to explain and verify the answers obtained. Course Review Horay (CRH) is a learning method that can create a festive and fun classroom atmosphere. In this case, experimental research was used. In this case it can be concluded that the Course Review Horay (CRH) is more efficient than the Problem Solving Method in learning Mathematics in Elementary Schools.